Analisis Framing Model Zhongdang Pan Dan Gerald M. Kosicki dalam Konstruksi Pemberitaan Wacana Calon Presiden 2024 di Indonesia - Munif, Muhammad Abdullah (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2023)
This research examines the Framing Analysis of the Zhongdang Pan and Gerald M. Kosicki Models in the News Construction of the 2024 Presidential Candidate Discourse in Indonesia This paper aims to determine the Framing of the Zhongdang Pan and Gerald M. Kosicki Models in the News Construction of the 2024 Presidential Candidate Discourse in Indonesia as seen from the point of view of the viva.co.and Suara.com media. The method of this study is a literature study by collecting books related to the news of the 2024 presidential candidate discourse. The results of this research viva.co and Suara.com in the Zhongdang Pan and Gerald M. Kosicki model have syntactic, script, thematic and rhetorical indicators. Both of these news did not contain graphic elements.